Case Report: A rare case of primary hepatic Castleman’s disease mimicking a liver tumor - Chen, Hong; Pang, Xiaoxi; Li, Jie; Xu, Baixuan; Liu, Yachao (Frontiers in Oncology, 2022)
Castleman’s disease (CD) is a primary lymphoproliferative disorder of the lymph nodes with rare extra-nodal primary affection. Solid organ involvement is rare, and isolated liver involvement is extremely rare. Here we presented a case of a 59-year-old woman with a hepatic lesion accidentally found by ultrasound. The MRI result indicated primary liver malignancy or liver metastases. 18F-FDG PET/CT could not exclude hepatic malignant tumor due to its high metabolism. Finally, the hepatic CD was confirmed by postoperative pathology.